2020
DOI: 10.1101/2020.11.09.374017
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Abbott ARCHITECT HIV Ag/Ab Combo Assay for Determining Recent HIV-1 Infection

Abstract: BackgroundGiven the challenges and costs associated with implementing HIV-1 incidence assay testing, there is great interest in evaluating the use of commercial HIV diagnostic tests for determining recent HIV infection. A diagnostic test with the capability of providing reliable data for the determination of recent HIV infection without substantial modifications to the test protocol would have a significant impact on HIV surveillance. The Abbott ARCHITECT HIV Ag/Ab Combo Assay is an antigen/antibody immunoassa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Since the literature lacks a clear value to define what a high CMIA is, a more conservative definition was assumed based on our tested cases, in which the cutoff was defined as a CMIA value above the median of volunteers lacking previous negative test, i.e., 821 units. This value is above the 400 units used in some previous studies as a proxy for chronic cases 13,14 .…”
Section: Methodsmentioning
confidence: 54%
See 1 more Smart Citation
“…Since the literature lacks a clear value to define what a high CMIA is, a more conservative definition was assumed based on our tested cases, in which the cutoff was defined as a CMIA value above the median of volunteers lacking previous negative test, i.e., 821 units. This value is above the 400 units used in some previous studies as a proxy for chronic cases 13,14 .…”
Section: Methodsmentioning
confidence: 54%
“…The recency cutoffs used were as suggested by the literature, such as defining recent infections by an avidity index below 40% 9 and a cut-off below 0.5% of the ambiguous positions 12 . For CMIA, although a signal/cut-off (S/CO) limit of 400 13 or 418 (IQR25-75 384-449) 14 units was used by some studies as a proxy for recent infection, a stringent cutoff of an S/CO below 200 units 15 was chosen.…”
Section: Methodsmentioning
confidence: 99%
“…Use of testing history alone could be a pragmatic approach to correct for seroconversion in countries lacking detailed clinical or serological information. Where collected, information from diagnostic tests could also provide a useful proxy for recency, recent studies have shown correlation between a ‘recent’ LAg result and a signal-to-cutoff ratio <250 in the widely-used Abbott Architect Ag/Ab assay [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%